Genetic relationship and similarity of some selected chicken strains (Journal of the Bangladesh Agricultural University, 2012)
Random amplified polymorphism DNA (RAPD) technique was applied to detect genetic similarity between seven local  chicken strains selected for eggs and meat production in Bangladesh. Conservation and improvement strategies     ought to be based on proper genetic characterization in association with phenotypic characterization. White Leghorn, White Rock, Rhode Island Red, and Barred Plymouth Rock fall under recognized strain and Hilly, Deshi and Necked Neck fall under native bird group. Based on four oligonucleotide primers, the genetic similarity between the eggproducing strains (White Leghorn; White Rock; Rhode Island Red and Barred Plymouth Rock) was between 81.3 to 89.3 %. While the genetic similarity of three native chicken strains selected for meat production (Hilly, Deshi and Necked Neck) was 69.0 to 78.7 % similar based on the RAPD Marker. So, RAPD markers appeared to be effective in detecting similarity between chicken strains and they provide a potential tool for studying the inter-strain genetic similarity.   DOI: http://dx.doi.org/10.3329/jbau.v9i2.10989   J. Bangladesh Agril. Univ. 9(2): 217220, 2011